Novel non-contact deformation health monitoring of towers and rotating composite based wind turbine blades using interferometric ground-based radar - Ochieng, Francis Xavier; Hancock, Craig Matthew; Roberts, Gethin Wyn; Le Kernec, Julien; Tang, Xu (2018)
This paper describes the use of non-contact quasi monostatic ground-based radar (GBR) for system health monitoring (SHM) of the blades of wind turbines. It focusses on the deflection monitoring of these blades and validates the results from the design parameters extracted from numerical simulations during the design stage. Using a 3-tier SHM framework, acquisition of deflection in the time-domain is done by the GBR. These results are then transformed into the frequency-domain using a fast Fourier transform (FFT) to obtain the resonant frequencies as second step in the 3-step SHM framework. The third step of validation / hypothesis testing of the measured results with initial simulated design parameter is then effected to demonstrate that the GBR can be used for deformation health monitoring of composite blades and towers. The work demonstrates that the GBR can be deployed as a non-contact, real-time monitor that can measure deflections and natural-vibration frequencies of wind turbines blades. This enables smart monitoring of dynamic structures in urban and non-urban settings.